2020
DOI: 10.1002/open.202000172
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Properties of trans‐1,3,3,3‐Tetrafluoro‐ propene (HFO‐1234ze) and 2,3,3,3‐Tetrafluoropropene (HFO‐1234yf) Refrigerants

Abstract: The refrigerant trans-1,3,3,3-tetrafluoropropene (HFO-1234ze) is used as a replacement for former cooling agents that have been phased-out due to their global warming potential or ozone depleting potential. Although it is used on a large scale, only a few vibrational data and no structural data of HFO-1234ze are known. We report structure determinations based on low-temperature single-crystal X-ray diffraction data as well as gas-phase diffraction data of HFO-1234ze and HFO-1234yf (2,3,3,3-tetrafluoropropene).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Within this gas family, tetrafluoropropene (C 3 H 2 F 4 ), which comes in different isomer forms [4], was of particular interest, mainly because two isomers, the HFO-1234ze and HFO-123yf, are currently used as refrigerants in the industry, making them rather available for purchase. The choice fell on HFO-1234ze due to the moderate flammability of the yf isomer.…”
Section: Introductionmentioning
confidence: 99%
“…Within this gas family, tetrafluoropropene (C 3 H 2 F 4 ), which comes in different isomer forms [4], was of particular interest, mainly because two isomers, the HFO-1234ze and HFO-123yf, are currently used as refrigerants in the industry, making them rather available for purchase. The choice fell on HFO-1234ze due to the moderate flammability of the yf isomer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, a new generation of fluorinated compounds, like hydrofluoroethers (HFEs) and hydrofluoroolefins (HFOs), is an acceptable alternative to CFCs. HFOs and HFEs are chlorine- and bromine-free compounds, , and because of their shorter lifetimes, they do not contribute significantly to ozone depletion. , Among fluorinated compounds, HFOs are promising alternatives, in particular for replacing conventional refrigerants, and are more highly reactive than HFCs due to the presence of carbon–carbon double bonds. , Hence, HFOs are easily oxidized in the atmosphere, thereby limiting their accumulation in the atmosphere. …”
Section: Introductionmentioning
confidence: 99%
“…Among the various HFOs, 1,1,3,3-tetrafluoroprop-1-ene (HFO-1234zc) is proposed for various commercial applications, especially in refrigerators, as industrial coolants, in air conditioners, and as fire suppression and cleaning agents. ,, Due to the presence of hydrogen atoms and −CC– bonds, it can be easily oxidized in the atmosphere by reacting with the OH radical. , A number of experimental and theoretical studies on the reaction of HFOs with the OH radical are reported in the literature. , Using the flash photolysis/resonance fluorescence technique, Orkin et al experimentally studied the reaction of CHFCH–CF 3 with the OH radical and reported a rate constant of 0.71 × 10 –12 cm 3 molecule –1 s –1 at 298 K. Ramanjaneyulu and Rajakumar theoretically studied the H-atom abstraction and OH-addition reaction of CF 2 CHCHF 2 by the OH radical and reported a total rate constant of 0.54 × 10 –12 cm 3 molecule –1 s –1 at 298 K. Papadimitriou et al studied the temperature-dependent oxidation reaction of CF 3 CFCH 2 with the OH radical over the temperature range 206–380 K and reported a rate constant of 1.12 × 10 –12 cm 3 molecule –1 s –1 at 296 K. The above results show the shorter lifetimes of HFOs than those of CFCs or HFCs . However, previous studies , have reported that fluorinated compounds emitted into the atmosphere effectively absorb the earth’s IR radiation and thus act as potent greenhouse gases and these gases contribute significantly to global warming.…”
Section: Introductionmentioning
confidence: 99%
“…In order to safely use these compounds in industry, extended studies into their properties and reactivity is advisable [3] . Furthermore, they might be considered as useful building blocks to generate molecules of higher value [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to safely use these compounds in industry, extended studies into their properties and reactivity is advisable. [3] Furthermore, they might be considered as useful building blocks to generate molecules of higher value. [4] One approach imparts the development of routes for main group or metal‐mediated functionalization including both C−F and C−H bond activation reactions.…”
Section: Introductionmentioning
confidence: 99%